Ekonomika SNG . Ekonomika SNG . Economics of CIS . Экономика СНГ - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Fiscal reforms in the Russian Federation; withdrawal of old banknotes from circulation; economic ties between Russia and Commonwealth of Independent States (CIS) countries; the problem of non-payments. Featured in the program: Solovov, Viacheslav Ivanovich (Deputy Head of the Central Bank of the Russian Federation) Contributors: Gerasimov, Kim (Anchor) Денежная реформа в Российской Федерации; изъятие из оборота денежных знаков старого образца; экономические связи России с другими странами Содружества Независимых Государств (СНГ); проблема неплатежей. В программе участвуют: Соловов, Вячеслав Иванович (Заместитель председателя Центрального банка Российской Федерации) Создатели: Герасимов, Ким (Ведущий/Ведущая)